2014
DOI: 10.5694/mja13.00186
|View full text |Cite
|
Sign up to set email alerts
|

Use of secondary stroke prevention medicines in Australia: national trends, 2003‐2009

Abstract: Increased use of secondary stroke prevention medicines was shown in this study, in accordance with national stroke guideline recommendations and initiatives supporting quality use of medicines in Australia. There may be opportunity to further increase use of these medicines among older Australians who have had a TIA or ischaemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Studies have reported long-term changes in the management of stroke risk factors for secondary prevention in North American and Australian populations [ 6 , 7 ]. However, there are no recent data on long-term trends in secondary stroke prevention from Europe and no available reports from countries after the economic transition.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported long-term changes in the management of stroke risk factors for secondary prevention in North American and Australian populations [ 6 , 7 ]. However, there are no recent data on long-term trends in secondary stroke prevention from Europe and no available reports from countries after the economic transition.…”
Section: Introductionmentioning
confidence: 99%
“…Separations indicating either inter- or intra-hospital transfers, a change in the type of care provided (for example, from acute to sub-acute care), death or discharge to home or other accommodation, were linked to form a continuous period of hospitalisation. As previously described, 8 contiguous episodes were joined if separated by up to 24 hours 17 or if recorded by the end of the next day if the preceding separation was recorded at another hospital.…”
Section: Methodsmentioning
confidence: 99%
“…A commonly used metric is to calculate the time taken for patients to refill scripts and estimate dosages by the application of the 75th percentile of refill times for each patient (PDD 75 ) 13–20 . However, as shown in a recent study that included a measure of the PDD based on the 80th percentile of the time taken until the next refill of various antihypertensive classes in patients with heart failure, 21 there may be substantial differences between PDC and 1DD estimates.…”
Section: Introductionmentioning
confidence: 99%